Cholinergic enhancement reduces orientation-specific surround suppression but not visual crowding - Kosovicheva, Anna A.; Sheremata, Summer L.; Rokem, Ariel; Landau, Ayelet N.; Silver, Michael A. (Frontiers in Behavioral Neuroscience, 2012)
Acetylcholine (ACh) reduces the spatial spread of excitatory fMRI responses in early visual cortex and the receptive field sizes of V1 neurons. We investigated the perceptual consequences of these physiological effects of ACh with surround suppression and crowding, two tasks that involve spatial interactions between visual field locations. Surround suppression refers to the reduction in perceived stimulus contrast by a high-contrast surround stimulus. For grating stimuli, surround suppression is selective for the relative orientations of the center and surround, suggesting that it results from inhibitory interactions in early visual cortex. Crowding refers to impaired identification of a peripheral stimulus in the presence of flankers and is thought to result from excessive integration of visual features. We increased synaptic ACh levels by administering the cholinesterase inhibitor donepezil to healthy human subjects in a placebo-controlled, double-blind design. In Exp. 1, we measured surround suppression of a central grating using a contrast discrimination task with three conditions: 1) surround grating with the same orientation as the center (parallel), 2) surround orthogonal to the center, or 3) no surround. Contrast discrimination thresholds were higher in the parallel than in the orthogonal condition, demonstrating orientation-specific surround suppression (OSSS). Cholinergic enhancement reduced thresholds only in the parallel condition, thereby reducing OSSS. In Exp. 2, subjects performed a crowding task in which they reported the identity of a peripheral letter flanked by letters on either side. We measured the critical spacing between the target and flanking letters that allowed reliable identification. Cholinergic enhancement had no effect on critical spacing. Our findings suggest that ACh reduces spatial interactions in tasks involving segmentation of visual field locations but that these effects may be limited to early visual cortical processing.